Pengaruh Psikoedukasi Tentang Manajemen Stress Dalam Meningkatkan Self Efficacy Keluarga Merawat ODGJ Di Wilayah Kerja Puskesmas Balowerti Kota Kediri - Eka Lutfiatus Solehah (STIKES ADVAITA MEDIKA TABANAN, 2021)
Beaground : The treatment of mental disorders is multifactorial, meaning that each treatment is interrelated and cannot work individually. For example, a patient who has received medication well, gets a good treament process at the horpital, but if he does get support from his family and environment, the patient my relapse. Destination : The Purpose of the study was determine the effect of providing psychoeducation on family self-efficacy in caring for ODGJ patients in the Balowerti Health Center Work Area, Kediri City. Method : The research design used is pre-experimental with pre-post-test design. The research variable is the provition of psychoeducation os the independent variable and self-efficacy as the dependent variable. the population is the entire family of ODGJ patients in the work area of the Balowerti Health Center, Kediri City, with 41 respondents. the research sample was taken with a total sampling technique of 41 respondents. Data were collected using a questionnaire sheet and processed by the Wilcoxon tes. Results : The results showed that before being given psychoeducation, most of the families with schizophrenia had low self-efficacy in treating patients with 17 respondents (77.3%) and after being given psychoeducation most had high self-efficacy as many as 18 respondents (81.8%). The results of the Wilcoxon test showed the value of = 0.00 < = 0.05 so that H0 was rejected so that there was an effect of giving psychoeducation to families in caring for schizophrenic patients affecting family self-efficacy to be better than before being given psychoeducation. Conclution : Providing psychoeducation can increase the information and insight that families have so that families can increase confidence and self-confidence in caring for family members with mental disorders.